Ten-Year Experience in the Treatment of Coarctation of the Aorta through Endovascular Stenting in Patients of Different Age Groups - Cherpak, Bogdan V.; Ditkivskyy, Igor O.; Yashchuk, Nataliia S.; Yermolovych, Yuliia V.; Golovenko, Oleksandr S.; Panichkin, Yuriy V. (Ukrainian Journal of Cardiovascular Surgery, 2021)
The aim. To analyze the 10-year experience in aortic coarctation endovascular stenting in patients of different age groups. Materials and methods. Examination and endovascular treatment of 194 patients aged 3 days to 60 years with coarctation of the aorta (CoA) with different anatomical and morphological variants was performed. According to the age criterion, the examined patients were divided into 4 study groups. The first group consisted of 84 patients (43.3%) over 25 years of age, group 2 included 33 patients (17.0%) aged 19 to 25 years, group 3 included 71 patients (36.6%) aged 5 to 18 years, and group 4 included 6 patients (3.1%) under 1 year of age. Results and discussion. We presented the clinical features of different anatomical and morphological variants of CoA. Endovascular treatment of CoA with stenting is considered the best method for adolescents and adults, due to the lower risk of aneurysm formation compared to balloon angioplasty. We were able to successfully reduce the invasive pressure gradient in patients of different ages and to establish the dependence of complication rate on the stent type used. The most common complications were aneurysm formation (2.1%) and stent migration (2.1%). Complications occurred more often in cases of uncovered stents compared to stent grafts (5.3% and 2.1%, respectively, p <0.05). No cases of hospital mortality were recorded in patients older than 5 years. Seven endovascular procedures were performed in 5 patients aged 3 days to 11 months (mean age 3.5 ± 1.6 months) with combined heart defects. Complications were documented in 1 child (20.0%). Endovascular intervention in pregnant women is indicated in refractory hypertension. We performed endovascular CoA stenting in 4 pregnant women at 15–23 weeks of gestation (average, 19.8 ± 3.1 weeks), and in 6 women with well-controlled hypertension stenting was performed within 48 hours to 5 years after delivery. In all the presented cases, successful revascularization was achieved. During follow-up (from 2 months to 10 years), all 10 women are alive, did not develop recoarctation or complications. Conclusions. The results of the analysis of CoA endovascular treatment showed that the chosen method and technique of intervention is appropriate and safe for patients of all ages, including pregnant women. Based on the results obtained, we have developed an algorithm for the management of patients who, according to clinical examination and echocardiography, were diagnosed with CoA during pregnancy.